Matthew 5:17 and Matthew's Community - Bradley Trout (HTS Teologiese Studies/Theological Studies, 2016)
One of the central arguments in establishing the ‘Christian-Jewish’ nature of the Matthean community is the argument that Matthew’s community was law observant. In particular, Matthew 5:17–19 is said to argue in favour of a community that had not broken ties with Judaism. This paper argues that Matthew 5:17–19 is not primarily about demonstrating lawobservance, but fulfilment. When πληρόω is understood in light of its broader Matthean usage, it becomes apparent that ‘to fulfil’ means the coming about of what the law and prophets anticipated. What is therefore in focus is not the conservative nature of the community, but the arrival of Israel’s hope. This is further demonstrated by the inclusion of ‘the prophets’, which also points to the coming of Jesus, as well as by the antitheses of 5:21–48, which demonstrates the Christological focus of the passage. More prominent than Jesus’ view of the law is the law’s (and prophets’) view of Jesus. An additional factor pointing in this direction is the prominence of the kingdom in this section of Matthew’s gospel. Following on from the declaration in 4:17, the kingdom of heaven remains central throughout the Sermon on the Mount, not least in 5:17–20. When this theological motif is taken into account, it confirms that 5:17–20 has in view the fulfilment of the Jewish hope that God’s kingdom would come. What God’s people have awaited – as anticipated in the law and prophets – has arrived. Reading this passage as if it were a treatise on the Matthean community’s view of the law overlooks the theological context and makes that which is peripheral (conservatism on the law) central, while what is central (fulfilment in that the kingdom has come) is made peripheral. This passage ultimately points to the newness brought about by Jesus and the kingdom of God. Scholars who find support for a conservative community in Matthew 5:17 have failed to reckon sufficiently with the nature of fulfilment in this passage.